Climatic Types, Their Distribution and Changes in Different Micro Meteorological Stations in Kathmandu Valley - Kattel, Dambaru Ballab (Nepal Journal of Science and Technology, 2010)
The objective of this paper was to organize the information, classify and resolute the altered frequency of climatic types of different micrometeorological stations in Kathamndu valley ( Kakani, Budhanilakantha, Godavari, Khumaltar, Airport, Panipokhari, Nagarkot, Khokana and Thankot). Analyzed data of the stations revealed the prevalence of "C'' (humid mesothermal)as the major type of climate. But the "Cwa" and "Cwb" types of climate were not common for all stations of Kathmandu valley. In some stations the "Cfa "and "Cfb" types of climate were also found. The temperature of Kathmandu valley has been increasing as above the trend of global warming but not alarming result of temperature increment was noticed. During 1976 to 2006, the altered of climatic types were found only at Godavari, Khumaltar, Panipokhari and Thankot, but the altered frequency was less during the period of 30 years. The average temperature in winter (11.55°C) and summer (23.78°C) was found maximum at the Airport as compared to other stations. The thirty years total seasonal precipitation in summer was maximum at Kakani (6890.12cm) and minimum at Khumaltar (2715.58cm). However, the seasonal precipitation in winter was found maximum at Thankot (205.58cm) and minimum at Khumaltar (151.69cm). Key words: Koppen's system; climatic types; temperature; precipitation; frequency analysis DOI: 10.3126/njst.v9i0.3183 Nepal Journal of Science and Technology 9 (2008) 171-178